Treatment of Congenital Myogenic Ptosis with Frontalis Suspension Surgery - Shaelva Lassa Sabatini; Riani Erna (Fakultas Kedokteran Universitas Sriwijaya, 2016)
Ptosis repair is a challenging oculoplastic surgical procedure that requires correct diagnosis, thoughtful planning, thorough understanding of eyelid anatomy, experience, and good surgical technique. Ptosis can causefunctional problem and cosmetic issue.Thisstudywasreport 2 cases of congenital myogenic ptosis which were treated with frontalis suspension surgery.Case report,a 11-year old and a 20-year old girl came to our clinic with chief complain drooping in the upper eyelid RE since their childhood. Patients also complained difficulty of reading. The degree of ptosis during the day was the same. No diplopia, dysphonia, dyspnea, and dysphagia. VA 20/20 in the both eyes. Ocular motility were normal. MRD1 0 mm, FP 5 mm, no upper eyelid crease, LF 4 mm, no lagophthalmos, eyelid lag present, upper eyelid RE higher than LE in down gaze, and Bells phenomenon normal. Light reflex of pupil positive and diameter 3 mm in standard room illumination. Schimer test and TBUT were within normal. We diagnosed these patients with congenital myogenic ptosis RE and performed frontalis suspension surgery with autogenous tensor fascia lata.Postoperative, for first patient we got MRD1 2 mm and FP 7 mm. For second patient we got MRD14 mm and FP 9 mm. Patients had no complain drooping in the upper eyelid RE and difficulty of reading anymore.Frontalis suspension surgery is a way to treat patient with congenital myogenic ptosis who have poor levator function.